Family Return Migration - Till Nikolka (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
This paper investigates the link between family ties and return migration using Danish full population register data. Couples returning from Denmark to the non-Nordic countries are positively selected with respect to income of the primary earner. Positive selection holds for male and female primary earners, but is weaker among dual earner couples and among couples with children. Results suggest that schooling considerations as well as factors related to cultural identity play a role for return decisions of couples with children.
Keywords: F22; J13; J61; 330; International migration; family migration; return migration; education